Mechanical Transport of the Norwegian-British-Swedish Antarctic Expedition, 1949–52 - Swithinbank, Charles (Polar Record, 1953)
The Norwegian-British-Swedish Antarctic Expedition was equipped with three amphibious Weasels (Light Cargo Carrier M29C, manufactured by the Studebaker Corporation) supplied by the British Army. Their performance was excellent, and few repairs were necessary. They had a bad start, however., by being immersed in sea water during the outward voyage. For at least a month the hulls and engine compartments were flooded, the water-level being above the oil filler gauge. The resulting corrosion was extensive and serious. The electrical system of each machine was put out of order, and most linkages and levers were rusted together. When this damage had been rectified, most subsequent repairs and replacements became necessary only as a result of fair wear and tear.